The darkest day - Wood, Tom, 1978- (Signet, 2015)
While carrying out a hit on a terrorist financier, Victor finds himself the target of an assassin who proves to be just as deadly as he is. Never one to let such a thing go, Victor sets about hunting down his attacker and those who sent her. She is Raven -- a freelance assassin with a dark past and hidden agenda. If Victor wants to stay alive he must find out who Raven really is and what she is truly after.